The influence of substrate treatment on load carrying capacity of Ti6Al4V Duplex Coating - Yusuf, Yusliza; Mohd. Rosli, Zulkifli; Mohamad Juoi, Jariah; Mahamud, Zainab; Kwan, Wai Loon (2013)
In this work, duplex coating is carried out by conducting microwave plasma nitriding on Ti6Al4V, followed by the deposition of hardcoating (CrN) using arc coating system. Plasma nitriding of Ti6Al4V alloy using microwave plasma technique, created a thick (~130µm) modified layer (case depth) at processing temperature of 700°C and 5 hour. The load carrying capacity of the duplex coating assessed using Rockwell-C test shows that case depth increase with an increased in process temperature and time for nitriding. Consequently, affect the formation of compound layer on the plasma nitrided specimen. Moreover, the formation of compound layer may lead to uneven distributions of the hardcoating (CrN) applied resulted in poor adhesion of hard coating - nitrided substrate.